A Rapid Cu Enrichment Mechanism from Cu-Bearing Brine in Kuqa Basin, Xinjiang, China: Controlled by Crystallized Sequence of Saline Minerals. (26th March 2021) - Cao, Yangtong; Xu, Haiming
Abstract : Sediment-hosted copper deposit is usually related to arid climate, ancient saline lake basin, and brine. The Kuqa Basin filled with giant-thickness evaporite units is located in the northern Tarim Basin, Xinjiang, China. It is famous for sandstone-hosted Cu deposits formed by synsedimentary processes. However, our recent studies reveal that Cu enrichment is closely related to brine on the surface of clastic rocks in the basin. It is shown that green Cu mineral coexisting with halite and gypsum occurred in the fractured fault belts of sandstones or was precipitated with halite on the surface of maroon clay in the scallops of sandstone. By SEM, EDS, and geochemical analysis methods on Cu-mineralized solid samples and brines, respectively, combined with previous geological evidence, our studies demonstrate that green Cu mineral is paratacamite, and it occurred with gypsum, halite, secondary glauberite, natural copper, and probably lead chloride on the fractured fault belts of sandstones or surface of clay. Meanwhile, the precipitation of paratacamite is controlled by a crystallized sequence of saline minerals accompanying with evaporated-concentrated course of brine in which gypsum, secondary glauberite, paratacamite, and halite are crystallized in turn. The Cu-bearing brine derived from meteoric waters and ancient seawater has a powerful capacity to leach metallic ions from its surrounding rocks and can be formed in a very short time (10 days is OK) in normal pressure and temperature conditions; also, the cycle of surface-Cu enrichment (mineralization) is only a few months (no more than 5). These indicate that a rapid Cu enrichment mechanism from Cu-bearing brine occurs on the earth's surface of the evaporite basin. The mechanism might be supposed to make an enormous amount of metal mineralization in a short time if considered from a large-scale spatial viewpoint. By contrast with the lengthy geological period, the short evolutionary cycle of Cu enrichment (mineralization) is obviously different from the previous cognition.